Skin-deep: The copyrightability of tattoos and addressing the ambiguity of South African Copyright Law on tattoos - Hassan, Shar? (Department of Commercial Law, 2024)
“My body is my journal, and my tattoos are my story.” – Johnny Depp Would it ever occur to you that a third party could claim ownership of your skin? That could be the case with art that has been inked into your skin, namely a tattoo. Although copyright law is an established and codified field of law, there are a few novel sub-categories that remain equivocal and unaddressed by South African courts. As a result of an erratic, expeditiously evolving society, new fields emerge and become rampant enough to cause unexpected problems as the law tries to catch up. The application of copyright law to tattoos is a particularly timely example, and the focus of this dissertation. Is a tattoo copyrightable? Who is the owner of the tattoo copyright? What rights does an owner possess? Can an owner enforce copyright, and if so, what is the scope of such enforcement? Infringements occur in what and how many ways? These are not the questions that come to mind when getting a tattoo. Despite the lack of court decisions in this area of the law, this dissertation concludes that tattoos indeed satisfy the requirements of copyrightability in South Africa — originality and reduction to material form. It also discusses the copyrightability of tattoos, the parties with an ownership interest in a tattoo, and potential infringements and remedies. This dissertation concludes by exploring proposed solutions to the ambiguity regarding tattoos within copyright law. While the focus of this thesis is on South African law, due to limited research and a lack of judicial guidance on tattoos in the South African context, South Africa will be compared to the US to provide additional insights into where South Africa falls short and where we may seek guidance from the US approach to fill the lacunae in our law.